Optimization of conditions for direct bio-hydrogen production from water hyacinth by clostridium diolis C32-KKU - Muanruksa, Papasanee; Khongsay, Nadda; Fiala, Khanittha (Asia-Pacific Journal of Science and Technology, 2016)
Water hyacinth contains cellulose and hemicellulose which can be used as a substrate for bio-hydrogen production. Clostridium diolis C32-KKU, a cellulolytic bacterium, was employed to directly ferment water hyacinth to bio-hydrogen. The objective of this study was to optimize the direct bio-hydrogen production from water hyacinth by C. diolis C32-KKU. Two operation modes for bio-hydrogen production i.e. static and shaking modes were investigated. The results showed that the shaking mode was more effective than the static mode for hydrogen production. The shaking mode was then used to optimize bio-hydrogen production by variation of initial pH (4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5 and 9.0) and initial water hyacinth concentration (5, 10, 15, 20, 25 and 30 g-dry weight (dw)/L). The maximum hydrogen production of 19 mL/L was obtained at the initial pH of 5.5 and water hyacinth concentration of 10 g-dw/L. The cellulase activity of 0.0081 unit/mL was obtained under the optimal condition. The results of this study showed that direct bio-hydrogen production from lignocellulosic materials could be feasible.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">